PEMASARAN INTERNAL DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA (Studi Kasus Mahasiswa STIE-SAK) - Karim, Kurniati (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
Internal marketing that properly done would have an impact on service quality, which furthercould increase customer satisfaction and customer loyalty. The aim of this research was to determine how much influence application internal marketing and service qualitywithcustomer satisfaction on STIE Sakti Alam Kerinci.This research used quantitative method since researcher wanted to determine the measurement of X and Y variable. Population in this study is 153 people. Sampling technique used is a probability sampling with using accidental sampling. Data analysis techniques in this study ismultiple regresion analysis and coefficient of determination analysis.Questionaires were used as a tool in data collection method. The findings show that all hypothesis were proved to be significant internal marketing and service qualitywith customer satisfaction on STIE Sakti Alam Kerinci. The implies that Y = 68,051 + 0,083 X1 + 0,062 X2. ttable is 2,006 with using (α = 5%).Internal marketing has t count3,717 and customer satisfaction has t count 2,026. Ftable is 3,06and has t count 4,787. Internal marketing and service qualityas simultan influence positive and significance tocustomer satisfaction on STIE Sakti Alam Kerinci.